Enhancing Technical Efficiency in Aquaculture: A Bibliometric Analysis and Literature Review - M, Ma’in; Napitupulu, DMT; Zulgani, Zulgani; Zamzami, Zamzami (Nomico, 2024)
Early 2024, fueled by rising demand, growing awareness of healthier animal protein, and technological advancements. With the global population expected to reach 9.7 billion by 2050, aquaculture, particularly freshwater fish farming, is pivotal in satisfying the increasing need for animal protein. As the third-largest aquaculture producer, Indonesia faces significant challenges in optimizing production, requiring advanced technology, farmer education, and environmentally sustainable practices. This study conducts a bibliometric analysis of the literature on technical efficiency in aquaculture, mapping out research trends, collaborations, and existing gaps. The findings highlight the critical role of technical efficiency in enhancing economic performance and promoting environmental sustainability. Factors such as farmer demographics, training, infrastructure, gender inclusion, and environmental adaptation are identified as key influencers of efficiency. The study emphasizes the necessity of a comprehensive understanding of technical efficiency across various regions and species, underscoring Indonesia's potential as a focal point for further research in this area. This knowledge is essential for improving practices and policies to meet future food security needs effectively.